2014
DOI: 10.1179/2047773214y.0000000131
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of the probable case definitions of dengue by WHO (2009) and the WHO-SEAR expert group (2011)

Abstract: Background The primary objective of this study was to find the performance of the 2009 probable case definition of dengue and compare it with the definition given by the WHO-SEAR expert group in 2011. Methods A cross-sectional study was conducted in Thiruvananthapuram district of Kerala, which is hyperendemic for dengue. A consecutive series of 851 participants defined by the selection criteria were recruited from the primary, secondary, and tertiary health care settings. Sensitivity, specificity, predictive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Dengue is the most rapidly expanding and spreading mosquitoborne viral disease in tropical and subtropical countries [1]. This disease is mainly transmitted by Aedes aegypti and Aedes albopictus [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue is the most rapidly expanding and spreading mosquitoborne viral disease in tropical and subtropical countries [1]. This disease is mainly transmitted by Aedes aegypti and Aedes albopictus [2].…”
Section: Introductionmentioning
confidence: 99%
“…This disease is mainly transmitted by Aedes aegypti and Aedes albopictus [2]. The incidence of dengue has increased by 30-fold in the past 50 years [1]. Approximately 2.5 billion people in more than 100 countries are currently under the risk of dengue viral infection, with the majority living in the Asia-Pacific region [3].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, that used WHO case definition of DEN as the standard and evaluated the same RDT that we have evaluated the sensitivity and specificity was reported very low, probably because of using the clinical criteria as reference marker, that itself is debatable . Moreover, it is reported that the RDTs have different sensitivity and specificity in primary and secondary infection, Timing and storage of specimen, and to the infection by different serotypes .…”
Section: Discussionmentioning
confidence: 89%
“…We were also not able to reevaluate the patients in the convalescent period due to the pragmatic diagnostic study outline and the dynamics of the Rio de Janeiro city’s health care system. Although the gold standard for dengue diagnosis would be pairing specific dengue IgM in acute and convalescent period, as proposed by WHO [ 11 ], recent studies have also exclusively used PCR as the reference test to evaluate early phase dengue [ 45 ], to evaluate clinical algorithms [ 46 ] or ELISA and NS1 tests [ 15 ].…”
Section: Discussionmentioning
confidence: 99%